(untitled) (Islamic Sciences Journal, 2023)
Jurisprudential issues contained in Tafsir: The Goal of Wishes, by Al-Kurani (T.: 398 AH) in Surat An-Nisa in Personal Status (a comparative study.) The idea of the research is to collect the jurisprudential issues contained in the interpretation of the goal of the wishes, and to clarify the sayings of the jurists from the four schools of thought with the Zaydiyyah and the Zahiriyya, and their liberation and the statement of the most correct ones and its justifications. We were keen not to be intolerant of a particular doctrine, and we chose from the sayings according to what appeared to us from the evidence, in order to reach the correctness, God bless our Prophet Muhammad and his family.